Limnological Condition of Koto Tibun Reservoir, Kampar District, Riau Province Based on Physical - Chemical Parameters - Ricky Christoper P. S; Asmika H. Simarmata; Clemens Sihotang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Koto Tibun Reservoir is one of the reservoirs that exist in Riau Province precisely on the road crossing Pekanbaru-Bangkinang km. 43, Kampar District. These reservoirs are used for agriculture irrigation, aquaculture water supply and other needs. The research aims to understand the limnological condition in the Koto Tibun Reservoir based on physical – chemical parameters was conducted from February - March 2018. There are 3 stations, namely Station 1 (riverine zone), Station 2 (transition zone), and Station 3 (lacustrine). Sample were taken once/week for a 3 weeks period. Water quality parameters measured were temperature, transparancy, depth, water current, DO, CO2 free, pH, nitrate and phosphate concentration. Result shown that the temperature was 25,3 - 25,6 0C, transparancy 75 - 79 cm, depth 3,11 -  3,54 m, water current 0,16 - 0,40 m/second, DO 4,78 - 5,62 mg/L, CO2 free 18,64 - 19,44 mg/L, pH 5, nitrate 0,186 - 0,193 mg/L and phosphate 0,093 - 0,113 mg/L.  Based on nitrate and phosphate concentrations in Koto Tibun Reservoirs waters can be categorize oligotrophic and mesotrophic - eutrophic conditions.Keyword : Koto Tibun Reservoir, Aquaculture, Water Quality, Trophic Status